Long-term clinical outcome and performance of transcatheter aortic valve replacement with a self-expandable bioprosthesis. (6th January 2020) - Testa, Luca; Latib, Azeem; Brambilla, Nedy; De Marco, Federico; Fiorina, Claudia; Adamo, Marianna; Giannini, Cristina; Angelillis, Marco; Barbanti, Marco; Sgroi, Carmelo; Poli, Arnaldo; Ferrara, Erica; et al.
Abstract: Aims : In the last decade, transcatheter aortic valve (TAV) replacement determined a paradigm shift in the treatment of patients with severe symptomatic aortic stenosis. Data on long-term TAV performance are still limited. We sought to evaluate the clinical and haemodynamic outcomes of the CoreValve self-expandable valve up to 8-year follow-up (FU). Methods and results : Nine hundred and ninety inoperable or high-risk patients were treated with the CoreValve TAV in eight Italian Centres from June 2007 to December 2011. The median FU was 4.4 years (interquartile range 1.4–6.7 years). Longest FU reached 11 years. A total of 728 died within 8-year FU (78.3% mortality from Kaplan–Meier curve analysis). A significant functional improvement was observed in the majority of patients and maintained over time, with 79.3% of surviving patients still classified New York Heart Association class ≤ II at 8 years. Echocardiographic data showed that the mean transprosthetic aortic gradient remained substantially unchanged (9 ± 4 mmHg at discharge, 9 ± 5 mmHg at 8 years, P  = 0.495). The rate of Grade 0/1 paravalvular leak was consistent during FU with no significant change from post-procedure to FU ≥5 years in paired analysis ( P  = 0.164). Structural valve deterioration (SVD) and late bioprosthetic valve failure (BVF) were defined according to a modification of the 2017 EAPCI/ESC/EACTS criteria. In cumulative incidence functions at 8 years, moderate and severe SVD were 3.0% [95% confidence interval (CI) 2.1–4.3%] and 1.6% (95% CI 0.6–3.9%), respectively, while late BVF was 2.5% (95% CI 1.2–5%). Conclusion : While TAVs are questioned about long-term performance and durability, the results of the present research provide reassuring 8-year evidence on the CoreValve first-generation self-expandable bioprosthesis.